ANALISIS PENERAPAN SISTEM REMUNERASI DI UNIVERSITAS BRAWIJAYA - Rusul, Ahmad Khitamur; Noermijati, Noermijati (Jurnal Management Risiko dan Keuangan, 2022)
Employee motivation in an agency is a big challenge for every leader, one example is the salary allowance which is regulated in the remuneration system. The Rectorate of Universitas Brawijaya is the center for high leadership ranks at the university level who are authorized throughout the university environment. Brawijaya University is one of the universities that implements the Remuneration System for State Civil Apparatus under its auspices. This study aims to find out how the remuneration system is implemented in all academicians of Universitas Brawijaya and the obstacles they face. This research was conducted by using interview techniques for employees of the Remuneration System Team, Chief Administrative Officer / Deputy Dean II in the faculty environment and in-depth data collection with the Remuneration System Team of Universitas Brawijaya. Data was collected through observation, interviews and documentation, then the data was processed using Miles Hubermann's data analysis technique which consisted of three stages, including: Data Reduction, Data Presentation and Conclusion Drawing. The results of the analysis show that the remuneration system is an inseparable part of Brawijaya University, especially for Brawijaya University employees in managing human resources, the remuneration system is the performance of employees for their contribution to Brawijaya University.